Working cooperatively on current challenges in teacher education - Ropohl, Mathias; Melle, Insa; Sommer, Katrin; Habig, Sebastian; Hollaender, Monika; Strippel, Christian Georg (Chemie Konkret - Forum für Unterricht und Didaktik, 2021)
The increasing heterogeneity of learning groups as well as the ongoing digitalization of education raise the question of how teacher education in chemistry can respond to these changes and optimally prepare future chemistry teachers. It is not only necessary to adapt the curricula, but also, and most importantly, to redesign courses. Against this background, a cooperative teaching project is currently being conducted repeatedly over three semesters at the three locations of the University Alliance Ruhr. The aim of the project is to realign the content of existing modules and to implement these modules across universities so that all participating students can benefit from site-specific expertise and teaching priorities. To this end, each university has prepared a part of the course curriculum in the form of a thematic introduction. The students afterwards planned and presented learning opportunities for these contents in the context of a project phase. After two semesters the experiences were that positive that this article reports on the conception of the teaching project as well as student products and first results from the course evaluation. First results show that the majority of students is highly satisfied with the course design. They especially emphasize the structure and design of the learning environment as being very positive. However, they would like to see even more interaction with the students from the other universities. For other locations, this teaching project can thus be a stimulus for possible changes in chemistry teacher education.
Created from Fastlane, WoS look-up